PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB UNTUK MEMBANTU SISWA MEMPERSIAPKAN UJI KOMPETENSI PEMBUATAN SURIMI - Eka Alimatus Sa'diyah; Sri Handayani; Dewi Nur Azizah (Jurnal Pendidikan, 2022)
The purpose of this study is 1) to determine the feasibility of website-based learning media on the competency test material for making surimi, 2) knowing the results of students' cognitive training on the competency test material for making surimi using website-based media, 3) knowing the results of students' cognitive training on the competency test material for making surimiusing e-modules, 4) knowing the differences in the results of students' cognitive training after using website-based media with e-modules. The method used is the ADDIE model and is implemented using the Intact-Group Comparison design in class XII majoring in Agroindustry at SMK N 1 Cibadak with cognitive aspects as research factors. The results showed that the website-based learning media was declared "Very Appropriate". Then there was an increase in the results of students' cognitive training in the experimental class with an n-gain value of 0.64 and the control class with an n-gain value of 0.55. Then the results of hypothesis show that there are difference in the results of students' cognitive training in the competency test material for making surimi using website-based learning media with e-modules.